CORRELATION OF CLINICAL AND DEMOGRAPHIC FACTORS WITH THE OCCURRENCE OF MYOCARDIAL INFARCTION AND CARDIAC ARREST IN OLDER PATIENTS AFTER MAJOR ELECTIVE VASCULAR SURGERY - Perić, Velimir; Golubović, Mlađan; Lazarević, Milan; Kostić, Tomislav; Stokanović, Dragana; Đorđević, Miodrag; Marjanović, Vesna; Milić, Dragan; Stošić, Biljana; Marinković, Marija; Nikolić, Nemanja (Acta medicae Medianae, 2022)
The risk stratification as a part of preoperative preparation of patients involves a series of diagnostic and therapeutic procedures with the main objective of reducing peri/post-operative morbidity and mortality. The aim of the study was to identify a wide spectrum of preoperative clinical and demographic characteristics which were significantly associated with the occurrence of myocardial infarction and cardiac arrest (MICA) during six-month period after vascular surgical procedure, during 2017, 2018, 2019, the study included 144 patients (96 men-66.6 % and 48 women-33.3 %) over 65 years of age (average 70 years). MICA in the first six months after the intervention was associated with higher NYHA class (p < 0.001), previous coronary artery disease (p < 0.001), cardiomyopathy (p < 0.05) or previous myocardial infarction (p < 0.05), usage of calcium channel antagonists (p < 0.05) and antiplatelet drugs (p < 0.001), higher ASA score (p < 0.01), higher urea concentration (p < 0.01), lower ejection fraction (p < 0.001) and longer intensive care unit stay (p < 0.001). Using binary logistic regression method, multivariate analysis has identified previous coronary artery disease as a predictor of MICA occurrence (p < 0.01). In the multivariate Cox-regression model (χ2 = 71.515, p < 0.001), there were six independent predictors of survival without MICA. Previous coronary artery disease is most significant preoperative risk factor for MICA occurrence. Variables related to heart failure and high urea concentration are independent predictors for MICA.